Effects of Treated Cow Dung Addition on the Strength of Carbon-Bearing Iron Ore Pellets - Qing-min Meng; Jia-xin Li; Tie-jun Chun; Xiao-feng He; Ru-fei Wei; Ping Wang; Hong-ming Long (Advances in Materials Science and Engineering)
It is of particular interest to use biomass as an alternative source of fuel in direct-reduction ironmaking to ease the current reliance on fossil fuel energy. The influence of cow dung addition on the strength of carbon-bearing iron ore pellets composed of cow dung, iron ore, anthracite, and bentonite was investigated, the quality of green and dry pellet was evaluated based on FTIR analysis, and the mechanism of strength variation of the reduced pellets was investigated by analysing the phase composition and microstructure using XRD and SEM. The results show that cow dung addition decreased the green pellet strength due to expansion of the amorphous region of the cellulose in the cow dung; however, the dry pellet strength increased substantially. In the process of reduction roasting, it was found that cow dung addition can promote aggregation of iron crystals and increase the density of the pellets, resulting in increased strength of the reduction roasted pellets, while excessive cow dung addition resulted in lower strength.